Informal Sector Migrants and Remittances: Questioning the Culture and Socio-Economic Impact - Adihartono, Wisnu (CIC Lembaga Riset dan Konsultan Sosial, 2023)
This paper discusses the socio-economic impact of informal sector migrants and their remintances. It is known that in 2018 informal sector workers amounted to 58.22 percent. This is of course very worrying. The informal sector is unorganized, unregulated, and mostly legal but unregistered. The motivation of workers who work in the informal sector is to earn enough income for survival. From an economic point of view, the existence of remittances can be said to be important because it is able to improve the family economy and for the progress of the recipient community. In addition to being one of the instruments of economic change, remittances also have a broad impact on social and cultural life for families, recipient communities and their areas of origin. In the context of migration, it is stated that remittances in developing countries are a form of migrant efforts in maintaining the continuity of socio-economic ties with the area of origin, even though they are geographically far apart. This research uses qualitative research methods, descriptive and direct observation which is only carried out in Jakarta by looking directly at how informal sector migrants work.